The deformation mechanism in the western Qiangtang terrane and its surroundings: evidence from magnetotelluric data - Gu, Jiangfan; Jin, Sheng; Dong, Hao; Wei, Wenbo; Ye, Gaofeng; Zhang, Letian (Frontiers in Earth Science, 2023)
The study of the Tibetan Plateau's lithospheric structure and deformation mechanisms is an attractive area of research. However, geophysical investigations of the western Qiangtang terrane and its surrounding areas have been limited. Here we present a 3-D crustal electrical structure, generated with magnetotelluric data focus on the western Qiangtang terrane and its surrounding area. The electrical structure suggests the Longmu Co-Gozha Co fault, once believed to be a major regional deformation boundary, may not have cut the crust. We estimated melt content and rheological parameters, showing ductile deformation is dominant in most of the study area, with block extrusion contributing to regional deformation. However, this model alone is insufficient to explain the current state of deformation. Viscous deformation regions formed by mantle melt upwelling cut through the ductile deformation region, turning it into small blocks and resulting in scattered deformation on the surface.